Antecedents of International Opportunity Recognition in Born Global Firms. (4th May 2017) - Kraus, Sascha; Niemand, Thomas; Angelsberger, Moritz; Mas-Tur, Alicia; Roig-Tierno, Norat
ABSTRACT: International opportunity recognition has become an important field of research in recent years. This study deals with the effects of entrepreneurial alertness, systematic search, prior knowledge, and social networks on first-time international opportunity recognition of entrepreneurs inside born global firms. In order to answer this research question, a quantitative survey within born global firms was conducted. The empirical results demonstrate that entrepreneurs of born global firms tend to recognize the first international opportunity through a combination of entrepreneurial alertness and systematic search. Furthermore, network relationships are essential for entrepreneurs within these firms because they can aid in identifying the initial international opportunity. The findings also illustrate that the entrepreneur's prior international knowledge as well as prior international experience positively contribute to the initial international opportunity recognition.